Equisetin is an anti-obesity candidate through targeting 11β-HSD1 - Zhenlu Xu; Dongyun Liu; Dong Liu; Xue Ren; Haibo Liu; Guihong Qi; Yue Zhou; Chongming Wu; Kui Zhu; Zhongmei Zou; Jing Yuan; Wenhan Lin; et al. (Elsevier, 2022)
Obesity is increasingly prevalent globally, searching for therapeutic agents acting on adipose tissue is of great importance. Equisetin (EQST), a meroterpenoid isolated from a marine sponge-derived fungus, has been reported to display antibacterial and antiviral activities. Here, we revealed that EQST displayed anti-obesity effects acting on adipose tissue through inhibiting adipogenesis in vitro and attenuating HFD-induced obesity in mice, doing so without affecting food intake, blood pressure or heart rate. We demonstrated that EQST inhibited the enzyme activity of 11β-hydroxysteroid dehydrogenase type 1 (11β-HSD1), a therapeutic target of obesity in adipose tissue. Anti-obesity properties of EQST were all offset by applying excessive 11β-HSD1's substrates and 11β-HSD1 inhibition through knockdown in vitro or 11β-HSD1 knockout in vivo. In the 11β-HSD1 bypass model constructed by adding excess 11β-HSD1 products, EQST's anti-obesity effects disappeared. Furthermore, EQST directly bond to 11β-HSD1 protein and presented remarkable better intensity on 11β-HSD1 inhibition and better efficacy on anti-obesity than known 11β-HSD1 inhibitor. Therefore, EQST can be developed into anti-obesity candidate compound, and this study may provide more clues for developing higher effective 11β-HSD1 inhibitors.